Fundamentals of petroleum refining - Fahim, M. A. (Elsevier Science, 2010)
Fundamentals of Petroleum Refining provides a thorough and balanced introduction to refinery engineering topics, from basic concepts and unit operations to overall refinery economics, planning and control. Based on the fundamentals of thermodynamics and kinetics, the text develops the scientific background needed to understand refinery operations, provides an in depth description of major refinery processes, and then assimilates an integrated refinery by focusing on the economic and operational aspects for enhancing performance and profitability. The book is mainly directed to undergraduate and graduate students in Chemical and Petroleum Engineering, Chemistry and Chemical Technology. It is also directed to new engineering college graduates who are starting their career in oil and gas industry. For experienced engineers and managers, this book is ideal for acquiring the necessary background in this area and following up with new topics in refining industry. The book includes topics such as clean fuels, gasification, biofuels, automation, environmental impacts as well as planning and scheduling of refinery operations. Throughout, the book provides numerous opportunities to put fundamental refining principles into practice. - Provides balanced coverage of fundamental and operational topics - Includes spreadsheets and process simulators for showing trends and simulation case studies - Relates processing to planning and management to give an integrated picture of refining.
Includes index.
Keywords: Petroleum -- Refining.; elektronické knihy; electronic books